Лазер на парах бромида железа - Суханов В. Б. Виктор Борисович; Шиянов Д. В. Дмитрий Валерьевич; Тригуб М. В. Максим Викторович; Димаки В. А. Виктор Анатольевич; Евтушенко Г. С. Геннадий Сергеевич (2016, 2016)
Заглавие с экрана